Analysis of Amoxicillin and Tetracycline Residues in Chicken Meat Using High Performance Liquid Chromatography-Mass Spectrometry - Furi, Mustika; Sinaga, Siti Morin; Putra, Effendy De Lux (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
Antibiotics are commonly used as food additives in broiler farms and their use tends to be excessive regardless and incorrect that can leave some antibiotic residues in chicken meat. The aimed of this study was to analyze on antibiotic residues level amoxicillin and tetracycline in chicken meat sold in Medan. The antibiotic residues analysis was conducted by extracting the antibiotic from chicken meat with water and acetonitrile (2:8, v/v) and detected by high performance liquid chromatography-mass spectrometry detector using C-18 column (4.6 mm i.d., length 30 mm, particle size 1.8 Âµm) at 35 oC, with the mobile phases, 0.1 % formic acid solution in water and 0.1 % formic acid solution in methanol with gradient elution technique at a flow rate of 0.5 ml/minute. The result exhibited that the chicken meat that were collected from five markets in Medan apparently contained antibiotic residues tetracycline . The level of tetracyclin residue in chicken meat was 0.1157-1.4436 Âµg/g, which exceed the maximum level for tetracyclin residue allowed in foodstuffs of animal origin which is 0.1 ug/g. Keywords: residue, antibiotic, amoxicillin, tetracycline, chicken meat